1996
DOI: 10.1074/jbc.271.3.1551
|View full text |Cite
|
Sign up to set email alerts
|

Circular Dichroism and X-ray Spectroscopies of Azotobacter vinelandii Nitrogenase Iron Protein

Abstract: A detailed description of the function of MgATP hydrolysis in the nitrogenase substrate reduction mechanism has yet to emerge (1-5). The current model suggests that MgATP hydrolysis is coupled to electron transfer between the nitrogenase component proteins, the iron protein (Fe protein), 1 and the molybdenum-iron protein (MoFe protein). It is known that the Fe protein can bind two MgATP molecules and that this binding results in protein conformational changes essential to Fe protein docking to the MoFe protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
62
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 35 publications
(29 reference statements)
5
62
0
Order By: Relevance
“…For this purpose in nucleotide-dependent switch proteins minor conformational changes are induced by ATP binding and hydrolysis. Such alterations have been shown for the related nitrogenase protein NifH 2 by various three-dimensional structural analyses (16) as well as by CD spectroscopy in the 350 -600 nm range (24,47).…”
Section: Epr Analyses Of [4fe-4s] Clusters In the Ternary Dpor Complementioning
confidence: 76%
See 2 more Smart Citations
“…For this purpose in nucleotide-dependent switch proteins minor conformational changes are induced by ATP binding and hydrolysis. Such alterations have been shown for the related nitrogenase protein NifH 2 by various three-dimensional structural analyses (16) as well as by CD spectroscopy in the 350 -600 nm range (24,47).…”
Section: Epr Analyses Of [4fe-4s] Clusters In the Ternary Dpor Complementioning
confidence: 76%
“…The spectral shape of ChlL 2 in the presence of nucleotides correlates well to CD spectra obtained in a related study for NifH 2 incubated with MgADP also showing positive deflections for the spectra visible at 340 and 480 nm. In contrast, ChlL 2 in the absence of nucleotides and ChlL 2 in the presence of ATP exhibited substantially different spectra when compared with nucleotidefree NifH 2 or NifH 2 in the presence of MgATP (24,47,48). From these experiments we concluded that ChlL 2 is a nucleotide-dependent switch protein triggering an ATPdependent conformational change that subsequently results in ternary complex formation.…”
Section: Epr Analyses Of [4fe-4s] Clusters In the Ternary Dpor Complementioning
confidence: 81%
See 1 more Smart Citation
“…Upon hydrolysis of MgATP to MgADP and P i , the Fe protein is proposed to undergo additional protein conformational changes (2). This is deduced from the observation that the MgADP-bound state of the Fe protein exhibits distinct spectroscopic properties for the [4Fe-4S] cluster compared with the MgATP-bound state (18,20,23). Thus, it has been suggested that the conformational changes induced within the Fe protein in going from the MgATP-bound state to the MgADP-bound state represent a molecular switch, which could be coupled to electron transfer and dissociation of the protein-protein complex (2).…”
mentioning
confidence: 99%
“…Full absorption spectra were recorded to confirm the oxidation state of the Fe protein and to determine the protein concentration. CD spectra were then recorded on an Aviv model 62DS spectropolarimeter and were base-line subtracted (18).…”
mentioning
confidence: 99%